Sociosemiotics as an impetus for naming - Valdet Hysenaj, (Technium Social Sciences Journal, 2020)
Albanian linguistics today finds itself in a new situation of studies and research in the continuation of the treatment of unexplored issues against the known ones, which as concepts have interacted following the path of a scientific axiom. Among the unspoken knowledge, like any other science, is semiotics (sociosemiotics, the field of our research) which is considered the "foundation of all sciences". It has the progress of constitution and development, but compared to many other sciences it is at the initiative of development. The paper will briefly address the emergence of this knowledge, its development and history, and then present the knowledge, understanding, goals, actions, basic concepts, main themes of treatment, importance, integration, primary areas of research, and sociosemiotic research as a motivating impetus. We have noticed that sociosemiotics not only has a study function for meaningful phenomena defined by the pragmatic dimensions of signs, but also has other additional effects such as p. sh. sociocultural, ethical, aesthetic, motivating, coordinating effects, etc. This can be seen from the internal motivational-subjective motivational impulses, based on pragmatic semiotics. We support the fact that sign theory is present in various fields of activity and creativity, so it is of scientific interest to investigate and analyze sociosemiotic indicators, which we have tried to address. Research in this field does not only belong to albanological knowledge, they, as seen in this paper, belong to many other sciences and are of particular interest for their further development. The lack of literature in the Albanian language for this knowledge is one reason that its research has not been conducted in research so far.